Building Bulk Heterojunction to Enhance Hole Extraction for High‐Performance Printable Carbon‐Based Perovskite Solar Cells. Issue 7 (29th April 2022) - Liu, Tongfa; Li, Yu; Xu, Rongguo; Lou, Lingyun; Gao, Jinqiang; Zhang, Kai; Su, Mingzhu; Qian, Wei; Wang, Gaopeng; Xiao, Shuang; Yang, Shihe
Abstract : An efficient perovskite junction is critical for the functioning of perovskite solar cells (PSCs). However, carbon‐based perovskite solar cells (C‐PSCs) have been plagued by the paucity of ways to construct an efficient junction between perovskite and carbon, staggering around an efficiency much lower than other state‐of‐the‐art PSCs. Herein, a perovskite/carbon bulk heterojunction (BHJ) for C‐PSCs is innovated and systematically studied. First, a two‐step orthogonal solvent method is developed to deposit a series of high‐quality perovskite films directly on the preformed perovskite film, allowing to manipulate compositions, band alignment, and charge transfer of the perovskite junction in a low‐cost and straightforward fashion. Second, by adopting this method to a porous carbon electrode as originally motivated, fabrication of perovskite/carbon BHJ with perovskite crystals by seamlessly filling in the porous carbon film is successfully done, thus providing a high contact area of perovskite/carbon heterojunction. Such a BHJ accelerates hole collection of the carbon electrode from the perovskite layer, thus significantly boosting the performance of C‐PSCs with MAPbI3 as the active layer from 12% to over 16% with certification. The device is shown to be stable with no obvious degradation after 1700 h of continuous light soaking near the maximum power point. Abstract : A two‐step orthogonal solvent method that enables straightforward fabrication of multilayer perovskite films is applied to construct the perovskite/carbon heterojunction for carbon‐based perovskite solar cells (PSCs). Such a bulk heterojunction (BHJ) improves the interface contact and facilitates the hole transport between perovskite and the carbon electrode, significantly boosting the power conversion efficiency (PCE) to 16.4% with certification.